2019
DOI: 10.4236/wjcd.2019.94023
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Pressure Flow Autoregulation

Abstract: The benefits or detriments of caffeine on the human cardiovascular system have not been thoroughly studied and are still poorly understood. In a world where caffeinated beverages are evidently the adult drug of choice (e.g. coffee, energy drinks, soda, tea), investigating its effects on our bodies is of great importance. In this study, we examined the effects of caffeine, taken as a tablet, on pressure-flow autoregulation. Young adults between 18 and 21 years of age were the experimental subjects. They were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…These results are consistent with earlier experimental investigations from which we have reported significant caffeine-mediated peripheral vasoconstrictor effects in humans. In two of the three studies ( [14], current report) we have observed caffeine-mediated blockade of local blood flow-regulating mechanisms, i.e. pressure-flow autoregulation [14] and reactive hyperemia (current report).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…These results are consistent with earlier experimental investigations from which we have reported significant caffeine-mediated peripheral vasoconstrictor effects in humans. In two of the three studies ( [14], current report) we have observed caffeine-mediated blockade of local blood flow-regulating mechanisms, i.e. pressure-flow autoregulation [14] and reactive hyperemia (current report).…”
Section: Discussionmentioning
confidence: 69%
“…In two of the three studies ( [14], current report) we have observed caffeine-mediated blockade of local blood flow-regulating mechanisms, i.e. pressure-flow autoregulation [14] and reactive hyperemia (current report).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations